Multiple surge trigger mechanisms of compound glacier: a case study on recent surges of Aru-4 Glacier, Western Tibetan Plateau - Weijin Guan; Bo Cao; Linwei Sha; Baotian Pan; Xuanru Zhao; Zongli Jiang; Guangjian Wu (Journal of Mountain Science, 2025)
Surge-type glaciers are widely developed in mountainous areas around the world. Understanding the trigger mechanism of glacier surge is a prerequisite for addressing their impacts on hydrological assessments, disentangling climate-glacier linkages, and mitigating downstream hazards. Most glacier surges occur in the compound glaciers; however, attention paid to the trigger mechanisms of such surges is minimal. This study confirmed two surges in the northern and southern branches of the Aru-4 glacier, respectively, in the Western Tibetan Plateau, using multisource remote sensing data. The northern branch of the Aru-4 glacier entered the active phase in 1999 and the active phase lasted for 6 years. The southern branch of the Aru-4 glacier entered the active phase in 2007 and the active phase lasted for 9 years. The southern branch of the Aru-4 glacier experienced a long period of retreat before the northern branch surged and their tongues were in a detached state. The northern branch surge carried a large amount of ice to the frontal area, blocking the downward transport of ice from the southern branch and initiated surge. Through the analysis of two surge processes of Aru-4 glacier, we found a new surge mechanism for compound glaciers. It was revealed that surges in such glaciers are not only triggered by the reduction in basal sliding resistance caused by the internal factors. These surges initiated in the upper part of the glacier then propagated to down glacier by intense compression force. Furthermore, surges can also be triggered by external intervention of blocking by other branches. This external trigger initiates the surge in the lower part of the glacier then propagated to the upper part by longitudinal traction force. In addition, comparing with the surge triggered by the internal factors, the surge triggered by the external intervention may have a more dramatic process.

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)